Influence of homocysteine on regulating immunothrombosis: mechanisms and therapeutic potential in management of infections - Aswathy S Nair; Lloyd Tauro; Harshit B Joshi; Arnab Makhal; Teddy Sobczak; Julien Goret; Antoine Dewitte; Srinivas Kaveri; Harinath Chakrapani; Maria Mamani Matsuda; Manjunath B Joshi (Inflammation Research, 2025)
Mechanisms controlling innate immune responses and coagulation are interdependent, evolutionarily entangled and make a complex network to form immuno-thrombosis axis which is an integral part of host-defence response. During infections, immunothrombosis generates intravascular scaffold enabling recognition, trap and destruction of pathogens facilitating tissue integrity. However, the accompanying dysregulation fosters into pathologies associated with thrombosis and regulates severity, morbidity and mortality in infections. Several extrinsic and intrinsic factors such as (epi)genetic mechanisms, age, metabolism and lifestyle regulate immunothrombosis during infections. Mounting evidence demonstrates that homocysteine, a metabolic intermediate of methionine synthesis pathway activate cells participating in immuno-thrombosis such as neutrophils, platelets, monocytes and endothelial cells. Interestingly, multiple infections are significantly associated with perturbed homocysteine metabolism. In the present review, we describe mechanistic insights into how homocysteine drives immuno-thrombotic crosstalk that generate a vicious cycle of inflammation and coagulation that fuels organ failure during infections with an emphasis on sepsis, COVID-19, and other infectious diseases caused by parasites, viral, and bacterial pathogens. Subsequently, we discuss therapeutic strategies targeting homocysteine metabolism that may improve clinical outcomes in infections.

On the Relationship Between Atmospheric Events of the Von Kármán Streets in the Robinson Crusoe Island and South Pacific Climate Variability - C. Amaya‐Cárcamo; C. Parada; B. Dewitte; M. Jacques‐Coper; S. Cornejo‐Guzmán (International Journal of Climatology, 2025)
The Juan Fernández Archipelago (JFA), located approximately 700 km off the Chilean coast, is of great scientific importance for its unique ecosystem and numerous endemic species. Designated a World Biosphere Reserve by UNESCO in 1977, it comprises three islands: Alejandro Selkirk (AS), Robinson Crusoe (RC) and Santa Clara (SC). Using satellite images of clouds, we identified and examined Von Kármán atmospheric vortex streets (VKSs) forming dipolar structures near the islands, a phenomenon rarely studied due to observational limitations. Based on visual inspection of satellite imagery, an average of three atmospheric VKSs events are recorded per year in the RC‐SC region over the period 2000–2020. Our study aims to characterise VKSs events in RC island through satellite observations and atmospheric reanalysis, while assessing their potential impact on the surrounding ocean dynamics using sea surface temperature (SST) data. We find that low‐level wind patterns, particularly prevalent in spring and summer, play a crucial role in the formation of VKSs, along with wind speeds that do not exceed 15 m/s. These conditions can occur during specific phases of regionally significant climate modes, such as the Interdecadal Pacific Oscillation (IPO), El Niño‐Southern Oscillation (ENSO), and variability in the subtropical South Pacific anticyclone. The activity of these modes is quantified by indices such as the Pacific Interdecadal Oscillation Tripole Index (TPI), Southern Oscillation Index (SOI), and South Pacific Subtropical Anticyclone Index (iASPS), highlighting a connection between VKS occurrence and large‐scale climate variability. We also observed elevated SST in the leeward RC during spring VKS events, potentially independent of the island mass effect. Our findings provide insights into the atmospheric and oceanic interactions shaping this unique island ecosystem.

Research advances and conservation needs for the protection of the Salas y Gómez and Nazca ridges: A natural and cultural heritage hotspot in the southeastern Pacific ocean - C.F. Gaymer; D. Wagner; R. Álvarez-Varas; B. Boteler; L. Bravo; C.M. Brooks; V. Chavez-Molina; D. Currie; J. Delgado; B. Dewitte; E.E. Easton; A.M. Friedlander; et al. (Marine Policy, 2025)

Environmental Drivers of Mesophotic Echinoderm Assemblages of the Southeastern Pacific Ocean - Ariadna Mecho; Boris Dewitte; Javier Sellanes; Simon van Gennip; Erin E. Easton; Joao B. Gusmao (Frontiers in Marine Science, 2021)
Mesophotic ecosystems (50–400 m depth) of the southeastern Pacific have rarely been studied because of the logistical challenges in sampling across this remote zone. This study assessed how oxygen concentrations and other environmental predictors explain variation in echinoderm assemblages at these mesophotic systems, where this group is among the predominant fauna. We compiled data on echinoderm taxa at 91 sampling stations, from historical and recent surveys (between 1950 and 2019), covering a longitudinal gradient of approximately 3,700 km along with the Nazca, Salas y Gómez, and Juan Fernández ridges. Uni- and multivariate model-based tools were applied to analyze the patterns of benthic fauna in relation to environmental factors. Our results indicate a significant positive relationship between echinoderm species richness and depth, oxygen, and salinity. Changes in echinoderm community composition were significantly explained by oxygen, longitude, and chlorophyll- a . We observed notable species turnovers at ∼101 and ∼86°W, where assemblages tend to be more variable across stations. This turnover possibly reflects the effects of physical barriers to dispersion (e.g., currents) and habitat changes. Echinoderm assemblages observed around Easter and Desventuradas Islands presented a high occurrence of potentially endemic taxa and distinct species assemblages. This study is the first to assess the structure of mesophotic echinoderm assemblages of the southeastern Pacific Ocean along a large spatial scale. The information reported here could help design appropriate management tools for the vast, recently created, marine protected areas in the southeastern Pacific.

Vertical structure variability and equatorial waves during central Pacific and eastern Pacific El Niños in a coupled general circulation model - B. Dewitte; J. Choi; S.-I. An; S. Thual (Climate Dynamics, 2012)

ENSO nonlinearity in a warming climate - J. Boucharel; B. Dewitte; Y. du Penhoat; B. Garel; S.-W. Yeh; J.-S. Kug (Climate Dynamics, 2011)

Statistical downscaling of sea-surface wind over the Peru–Chile upwelling region: diagnosing the impact of climate change from the IPSL-CM4 model - K. Goubanova; V. Echevin; B. Dewitte; F. Codron; K. Takahashi; P. Terray; M. Vrac (Climate Dynamics, 2011)